Contenido de ácidos grasos saturados y trans en materias primas grasas empleadas en algunas panaderías de Medellín (2018)
ABSTRACT: Previous studies have reported the presence of saturated and trans fatty acids in bakery products, which are related with chronic non-communicable diseases. Currently, the origin and quality of the primary fat ingredients and products used by bakers in the city of Medellin is currently unknown. Objective: The aim of this paper is to characterize the primary fat ingredients used for the preparation of bakery products. Materials and Methods: An exploratory transversal descriptive study, with 24 bakery samples belonging to three groups according to socioeconomic level. For each sample, a survey was conducted to evaluate the quality of fat and an analysis by gas chromatography was done to quantify 17 saturated and trans fatty acids was. Results: The average trans fatty acid content in the margarines is 0.46 g per 100 g, however regulatory entities allow 5 g per 100 g (Resolución 2508 de 2012, del Ministerio de Salud y Protección Social); 42.1% of fat content comes from saturated fatty acids and some primary fat ingredients do not comply with current regulations for packaged foods. Conclusions: None of the 24 fat ingredient chromatographic evaluations was quantified with trans fatty acids content higher than that allowed by Resolution 2508. This proves the effort of the food industry, however it is necessary to maintain the surveillance of the labeling to ensure compliance.